A rare case of carbimazole-induced hepatitis in a patient with Graves' disease. (22nd September 2015) - Burgin, Sarah; Zanetto, Ulises; Cooney, Rachel; Basu, Ansu
Although carbimazole-induced hepatitis is rare, clinicians should be aware of this potential complication and offer alternative treatment early.